VIEXPAND – Industrial Video for Expanded Vision in Remote Operations - Ribeiro, Carlos; Gil, João; Bento, Xavier; Figueiredo, Monica; Rosa, José; Antonio, Ruben; Ferreira, Lino; Assuncao, Pedro (International Journal of Industrial Engineering and Management, 2024)
Manufacturers are always looking for new ways to minimize breakdowns and failures to improve productivity and efficiency of the production process. VIEXPAND is a multiview AI-enhanced video processing and transmission system, operating in real-time, for industrial supervision, inspection, surveillance and security applications, on the road to Industry 4.0. It focuses on professional applications where remote monitoring of large industrial areas requires wide fields of view and multiple views, demanding for efficient data transmission, in real-time. This paper covers a use case in a glass bottle production industry to reduce raw material use and energy waste, increase production efficiency and improve safety of operations. Article history: Received (September 13, 2023); Revised (July 30, 2024); Accepted (September 3, 2024); Published online (October 4, 2024)